2009
DOI: 10.1007/s00406-009-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of initial seizure thresholds in electroconvulsive therapy

Abstract: In electroconvulsive therapy (ECT), electrical dosage is determined using 'fixed-dose', 'age-based' dose, or empirical titration methods. Estimation of initial seizure threshold (IST) has been claimed to be imperative for suprathreshold dosing. This systematic review aimed to determine common levels of IST, to define cut-off values for high IST, and to summarize reported IST associated factors. Medline and PsycINFO were searched from 1966 to January 2008 and relevant references were cross-checked. Subject head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 54 publications
4
17
2
Order By: Relevance
“…These results, however, cannot be directly compared because of differences in ECT device and titration schedule. A recent meta‐analysis including various races and areas concluded that ST had a wide distribution and the mean ST was 111.6 mC . The Consortium for Research in ECT (CORE) study with a large sample size reported a mean ST of 127 mC, which is close to the present result.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results, however, cannot be directly compared because of differences in ECT device and titration schedule. A recent meta‐analysis including various races and areas concluded that ST had a wide distribution and the mean ST was 111.6 mC . The Consortium for Research in ECT (CORE) study with a large sample size reported a mean ST of 127 mC, which is close to the present result.…”
Section: Discussionsupporting
confidence: 85%
“…Clearly, the relationship between history of ECT and alterations of ST needs further elucidation. Although BMI, antipsychotics, antidepressants, anticonvulsants, and lithium have been identified as potential factors, these were not found to have a significant influence on ST in the present study. Only 11% of the present subjects were prescribed certain anticonvulsants, meaning that they might have had a less significant influence on ST compared to benzodiazepine medication.…”
Section: Discussioncontrasting
confidence: 75%
“…The initial ST (IST) has been defined as the smallest electrical dose needed to produce a generalized seizure of at least 25–30 s on an electroencephalogram (EEG) at the first session [1, 8]. IST is reported to vary substantially between patients [2], although prospective studies are sparse [4, 32]. …”
Section: Introductionmentioning
confidence: 99%
“…Stimulus dose, age, sex, treatment number, and psychotropic medication affect seizure duration. Age and treatment number are inversely correlated with seizure duration, and seizure threshold is higher in men relative to women 69. Each psychotropic medication has an effect on seizure threshold by increasing or decreasing it, and anesthetics for sedating patients during ECT also influence this threshold 10–14…”
Section: Introductionmentioning
confidence: 99%